2011
DOI: 10.2527/jas.2011-3948
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting storage stability of various commercial phytase sources1,2

Abstract: SummaryA 360-d study was performed to evaluate the effects of environmental conditions on storage stability of exogenous phytases. Coated and uncoated products from 3 phytase sources (Ronozyme P, OptiPhos, and Phyzyme) were stored as pure forms, in a vitamin premix, or in a vitamin and trace mineral (VTM) premix. Pure products were stored at 0, 41, 73, and 99ºF (75% humidity). Premixes were stored at 73 and 99ºF. Sampling was performed on d 0, 30, 60, 90, 120, 180, 270, and 360. Sampling of the pure products s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
2
10
1
Order By: Relevance
“…The results of the present study demonstrated that, there were no significant differences (P> 0.05) in enzyme stability between the two types of xylanase products examined here. This might be due to that the xylanase in both products had resulted from the dried extract of the same source of fungi (Trichoderma longibrachiatum).In harmony with the present results, Sulabo et al (2011) reported that when phytase is stored at room temperature (23 °C) or lower, the pure product retained most (approximately 85%) of its activity for up to 60 days of storage regardless of phytase source.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the present study demonstrated that, there were no significant differences (P> 0.05) in enzyme stability between the two types of xylanase products examined here. This might be due to that the xylanase in both products had resulted from the dried extract of the same source of fungi (Trichoderma longibrachiatum).In harmony with the present results, Sulabo et al (2011) reported that when phytase is stored at room temperature (23 °C) or lower, the pure product retained most (approximately 85%) of its activity for up to 60 days of storage regardless of phytase source.…”
Section: Discussionsupporting
confidence: 89%
“…There are several enzyme products in the market; however, few scientific studies have been carried out to examine the potency of exogenous feed enzymes added as enzyme preparation, vitamin premix, mineral premix or vitamin and mineral premix (Iyer and Ananthanarayan, 2008;Sulabo et al, 2011). It will be more beneficial to include enzymes in a premix with vitamins, minerals or both as it makes them easier to test and may decrease the price of the diet formulation.…”
Section: Introductionmentioning
confidence: 99%
“…From a practical point of view, it is an important criterion that an enzyme designed for use in animal feed should survive storage at ambient temperature (Francesch and Perez-Vendrell, 1997; Sulabo et al, 2011). As shown in Figure 6, the storage stability at 37°C was greatly improved by immobilization.…”
Section: Resultsmentioning
confidence: 99%
“…Today, the feed industry mainly ascribes the rapidly expanding global market for animal feed enzymes to increased use of exogenous phytases (Sulabo et al, 2011). In conclusion, the T4 phytase may have great potential for use as an eco-friendly feed additive to enhance the nutritive quality of phytate and reduce phosphorus pollution, because it possesses high selectivity on the genuine phytate substrate, Mg-InsP 6 , and desirable activity profiles at physiologically-relevant pH and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Virtually, phytases are now added routinely to swine and poultry diets as an economical aid in the digestibility of phosphorus and an important measure for environmental protection (Selle and Ravindran, 2007). Currently, a number of microbial phytases with different enzymatic properties are commercially available (Sulabo et al, 2011). Catalytically, most bacterial, fungal, and plant phytases belong to the family of histidine acid phosphatases (HAP) typically characterized by a conserved active site motif, RHGXRXP (Lei and Porres, 2003).…”
Section: Introductionmentioning
confidence: 99%